Dampak Kebijakan Investasi dan Kebijakan Pendanaan terhadap Kebijakan Dividen - Pontoh, Winston (JURNAL RISET AKUNTANSI DAN AUDITING "GOODWILL", 2014)
Investors as shareholder has motivation for increasing their wealth through dividend that they would received or for increasing their investment value through increasing of their share in the market. Financing decision and investment decision is the very important information for investors, because these decisions are the basic decisions to reach the net earnings target and then become a base to determine the dividend payment. This study had samples for 270 companies in period of 2009 till 2011, where the method of analysis for hypothesis testing is using logistic regression method. This study found that, partially, the financing decision had significant relationships to dividend policy. And as general, this study found that, the samples by this study, tend to use less external financing but had more tangible assets.